3(y-9)-1=-2(-7y+9)-3y

Simple and best practice solution for 3(y-9)-1=-2(-7y+9)-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-9)-1=-2(-7y+9)-3y equation:



3(y-9)-1=-2(-7y+9)-3y
We move all terms to the left:
3(y-9)-1-(-2(-7y+9)-3y)=0
We multiply parentheses
3y-(-2(-7y+9)-3y)-27-1=0
We calculate terms in parentheses: -(-2(-7y+9)-3y), so:
-2(-7y+9)-3y
We add all the numbers together, and all the variables
-3y-2(-7y+9)
We multiply parentheses
-3y+14y-18
We add all the numbers together, and all the variables
11y-18
Back to the equation:
-(11y-18)
We add all the numbers together, and all the variables
3y-(11y-18)-28=0
We get rid of parentheses
3y-11y+18-28=0
We add all the numbers together, and all the variables
-8y-10=0
We move all terms containing y to the left, all other terms to the right
-8y=10
y=10/-8
y=-1+1/4

See similar equations:

| -x=x+7(x-2) | | 9k-4-2k=6k+3 | | -3(3x-4)=-9x-12 | | 2(5m-2)=-24 | | 2(x-4)=4* | | 3/x+5=-27/x-5 | | (5x+6)1/2=9 | | (x+42)+(2x+)=90 | | 5n2-3n=26 | | 12=-16x^2+14x+12 | | 0.8r-5.04=1.12 | | -3(2u-4)+7u=7(u+2) | | 2+x/11=-3 | | 15f=70 | | 6+x)1/2=7 | | 21=-5m-9 | | 0=8t^2+40t+5 | | 14x^2+6x+2x=0 | | 8y+4=92 | | 4n+4=-8(7n-8 | | 2x-11=x=0 | | (4+x)1/2=3 | | 14x^2-6x+2x=0 | | 16.6-c=-0.18 | | 12x-4=-38 | | -3(w+3)=3w-1+4(3w+1) | | 19+1+5x=9x-3 | | 7+35=21x+11 | | (16+10x)3/4=6 | | 5x÷4= | | 7w+3=5w+11* | | 3(2h+2)=2(3h+3) |

Equations solver categories